2017
DOI: 10.2174/1570159x15666170413115754
|View full text |Cite
|
Sign up to set email alerts
|

Aripiprazole, A Drug that Displays Partial Agonism and Functional Selectivity

Abstract: Background: The treatment of schizophrenia is challenging due to the wide range of symptoms (positive, negative, cognitive) associated with the disease. Typical antipsychotics that antagonize D2 receptors are effective in treating positive symptoms, but extrapyramidal side-effects (EPS) are a common occurrence. Atypical antipsychotics targeting 5-HT2A and D2 receptors are more effective at treating cogni-tive and negative symptoms compared to typical antipsychotics, but these drugs also result in side-effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
49
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(55 citation statements)
references
References 164 publications
1
49
1
1
Order By: Relevance
“…Additionally, serotoninergic pathways have a stimulatory effect on prolactin release . ARI acts as a partial agonist at DRD2 and 5‐HT1A receptors and as an antagonist at 5‐HT2A . It binds to the D2 receptor with the same affinity than dopamine if it is not present.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Additionally, serotoninergic pathways have a stimulatory effect on prolactin release . ARI acts as a partial agonist at DRD2 and 5‐HT1A receptors and as an antagonist at 5‐HT2A . It binds to the D2 receptor with the same affinity than dopamine if it is not present.…”
Section: Discussionmentioning
confidence: 99%
“…42 ARI acts as a partial agonist at DRD2 and 5-HT1A receptors and as an antagonist at 5-HT2A. 2 It binds to the D2 receptor with the same affinity than dopamine if it is not present. On the contrary, if dopamine is present, it shows functional antagonist activity.…”
Section: The Effect Of Aripiprazole On Prolactin Secretionmentioning
confidence: 99%
See 2 more Smart Citations
“…Aripiprazole was approved by the FDA in 2004 for treatment of bipolar disorder. 7 An important meta-analyses which was designed by Dian-JengLi and co-authors confirmed the efficacy or safety of aripiprazole in manic episodes. 8 There are several studies that show long-term administration of aripiprazole in combination to lithium or valproate in bipolar mania is well tolerated and safe and this improvement in functioning is maintained.…”
Section: Introductionmentioning
confidence: 95%